Transmission electron microscopy investigation on dislocation bands in pure Mg. (15th March 2017) - Jain, J.; Cizek, P.; Hariharan, K.
Abstract: In the present study, the evidence of complex dislocation band formation in pure Mg has been reported. The transmission electron microscopy investigation suggests that the double cross-slip of < c + a > screw dislocations plays an important role in the evolution of dislocation structure within these bands. The existence of dislocation bands is explained on the basis of instability of slip on a basal slip system, which results in sudden propagation of slip on pyramidal planes. Graphical abstract: